Model predictive load–frequency control taking into account imbalance uncertainty. (August 2016) - Ersdal, Anne Mai; Imsland, Lars; Uhlen, Kjetil; Fabozzi, Davide; Thornhill, Nina F.
Abstract: Nonlinear model predictive control (NMPC) is investigated for load frequency control (LFC) of an interconnected power system which is exposed to increasing wind power penetration. The robustified NMPC (RNMPC) proposed here uses knowledge of the estimated worst-case deviation in wind-power production to make the NMPC more robust. The NMPC is based on a simplified system model that is updated using state- and parameter estimation by Kalman filters, and it takes into account limitations on among others tie-line power flow. Tests on a proxy of the Nordic power system show that the RNMPC is able to fulfill system constraints under worst-case deviations in wind-power production, where the nominal NMPC is not. Abstract : Highlights: A nonlinear MPC (NMPC) is designed for load frequency control (LFC) of a power system. The NMPC is robustified (RNMPC) against variations in wind-power production. The controller is tested on a proxy of the Nordic power system. Results show that the RNMPC fulfills system constraints, while the NNMPC does not.